Age, Labor Force, and State Per Capita Incomes, 1930, 1940, and 1950 - Hanna, Frank A. (The Review of Economics and Statistics, 1955)
QTATE per capita incomes are computed by dividing estimated income payments to the residents of a state by the state's total population at midyear.1 This computation implicitly assumes that the denominator, total population, does not vary from one state to another in any important way. Yet it is known that states vary with respect to family size and composition, birth and death rates, participation in the labor force, and a host of other demographic attributes. It is the purpose of this paper to investigate the extent to which state differences in two of these attributes age composition and participation in the labor force -help to explain differences in state per capita incomes. Attention is confined largely to describing the direct effects on the distribution of per capita incomes among states of using alternative denominators that take account of variations in age composition and labor force participation. The study is confined to the three years, I930, I940, and I950 for which both Census data and official state income payment estimates are available.